AN ISRAELI–PALESTINIAN–JORDANIAN CONFEDERATION: Courage in the Face of Adversity. (December 2022) - Omar, Majeda
In light of the mounting sense of hopelessness and frustration due to the steady deadlock in efforts for solving the Palestinian–Israeli conflict, several proposals have been advocated in this regard with the aim of arriving at a final solution to this intricate conflict. This article examines the current proposal of an Israeli–Palestinian–Jordanian confederation presented by Prof. Alon Ben-Meir and provides some constructive remarks on a number of themes considered in his proposal.